Public policy and unemployment in interwar France: an empirical approach - Syme, T (University of Oxford, 2000)
This paper introduces an empirical model of the French interwar labour market that is comparable to models developed for the British labour market for this period, yet incorporates specific extensions in order to capture the peculiarities of the French case. The result is a model that can very accurately stimulate the movement of unemployment in the 1920s and 1930s and this is used to run a series of counterfactual simulations to estimate the labour market effects of various public policies adopted at the time. Of particular note is the result that the repatriation drive of the early 1930s had no significant effect on the size of foreign labour force by 1936 and that the decision to remain on the Gold Standard until 1936 raised unemployment each year by more than primary policies introduced to combat unemployment - public works and repatriation of foreign workers - reduced it.